Neuroscience and market dynamics: The impact of smoking withdrawal syndrome on the stock performance of tobacco companies - Evangelos Vasileiou; Christos Floros; Konstantinos Gkillas Gillas (Review of Economic Analysis (REA), 2025)
This study investigates the effect of the annual 'No-Smoking Day' on the stock performance of British American Tobacco (BATS) and Imperial Brands (IMB) from 1997 to 2023. Our findings reveal a significant negative impact of No-Smoking Wednesdays on BATS, with a moderate but statistically significant effect on IMB. To enhance robustness, we also perform a panel data analysis, which underscores the consistent negative effect of No-Smoking Day on the tobacco sector as a whole. These results suggest that No-Smoking Day generates a calendar-based effect on stock prices, challenging the Efficient Market Hypothesis. Beyond the behavioral effects tied to the anti-smoking campaign, this study introduces a novel perspective by linking investor behavior with neurological factors, particularly Nicotine Withdrawal Syndrome (NWS). NWS, characterized by irritability, anxiety, and mood disturbances, may influence investor sentiment, even among smokers who do not intend to quit. These withdrawal symptoms could induce stress and emotional responses, thereby affecting investor behavior and contributing to negative returns. Our findings align with prior behavioral studies and highlight the role of both psychological and neurobiological factors in shaping market dynamics. Future research should examine the combined effects of anti-smoking campaigns and NWS on investor behavior and market outcomes. Additionally, the varying statistical significance across firms suggests that the diversification of tobacco companies into non-traditional products warrants further investigation.
Keywords: D9; G12; G20; G41; 330; Neuro-Finance; Behavioral Finance; Rationality; Tobacco Industry; Market Efficiency; Investors Decision Making